VEGETATIVE PROPAGATION FROM SHOOT CUTTINGS OF MATURE ROSEWOOD TREES (ANIBA ROSAEODORA DUCKE) - Botelho, Camilla Martins; Quisen, Regina Caetano; Sampaio, Paulo de Tarso Barbosa (Floresta, 2024)
The production of seedlings by cuttings is an alternative to reconcile exploration and conservation of Rosewood (Aniba rosaeodora Ducke). In this study, our objective was to evaluate the rooting of cuttings from epicormic shoots of adult rosewood strains, through substrate tests, auxin concentrations, and cutting types, as well as to describe the anatomical process of the formation of adventitious roots. We carried out two experiments: E1 - substrate test (sand [A], vermiculite [V], and A+V) and concentrations of indole butyric acid (IBA) via talc (0.0; 1.5; 3.0; 6 .0 g kg-1); E2 – evaluation of the type of cutting: apical, intermediate, basal and regrowth; in addition to anatomical analyzes on samples of rooted cuttings. In the experiments, the variables survival (%), rooting (%), number of roots, and length of the largest root (cm) were evaluated. In E2, shoots (%), number of shoots, length of the largest shoot (cm), and callosity (%) were added. The rooting at 3.0 g kg-1 IBA was better than the control and vermiculite as a substrate was superior to sand. Even without interaction, auxin showed a tendency for better rooting when used with one of the vermiculite substrates. Among the types of cuttings, the regrowth was superior for most variables, differing from the others in terms of sprouting and callosity, while the basal was inferior in the concentration of total carbohydrates and starch.